Bridges not walls : a book about interpersonal communication - Stewart, John Robert, 1941- (Dubuque, Iowa : McGraw-Hill Humanities/Social Sciences/Languages, 2012)
"Since the first edition in 1973, Bridges Not Walls has examined the power and promise of interpersonal communication in intimate relationships, families, communities, and cultures. The text presents a broad range of scholarly and popular articles drawn from several disciplines, including communication, psychology, and philosophy, all chosen for their understandability and practical applicability. Within these readings are thought-provoking discussions of interpersonal contact, identity-management, verbal and nonverbal cues, perception, listening, assertiveness and self-disclosure, family communication, intimacy and social support, defensiveness and hurtful communication, conflict management, culture, and dialogue. Together, the readings emphasize the social and relational elements of human communication, the overlapping influence of verbal and nonverbal cues, the prominence of culture, and the close connection between quality of communication and quality of life"--
Machine generated contents note: Part One: Foundations of Interpersonal CommunicationChapter 1 Introduction to the Editor and To This BookChapter 2 Communication and Interpersonal Communication Chapter 3 Communication Building Identities Chapter 4 Verbal and Nonverbal Contact Part Two: Making Meaning TogetherChapter 5 Inhaling: Perceiving and Listening Chapter 6 Exhaling: Expressing and Disclosing Part Three: RelationshipsChapter 7 Communicating with Family and Friends Chapter 8 Communicating with Intimate Partners Part Four: Bridges Not WallsChapter 9 Coping With Communication Walls Chapter 10 Conflict: Turning Walls Into Bridges Chapter 11 Bridging Cultural Differences Chapter 12 Promoting Dialogue PHOTO CREDITS -- INDEX.
Keywords: Interpersonal communication; Language arts & disciplines / Speech